2018
DOI: 10.1155/2018/6362426
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Generation in Human Cells by a Novel Magnetic Resonance Imaging Contrast Agent

Abstract: The novel positive-contrast magnetic resonance imaging (MRI) marker C4 consists of an aqueous solution of cobalt chloride (CoCl2) complexed with the chelator N-acetylcysteine (NAC). We evaluated whether the presence of C4 or its components would produce reactive oxygen species (ROS, including hydroxyl, peroxyl, or other reactive oxygen species) in cultured cells. Human cancer or normal cells were incubated with 1% (w/v) CoCl2·6H2O or 2% NAC or a combination of both (1% CoCl2·6H2O : 2% NAC in an aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To further confirm whether IRTO can reflect the change of the mitochondrial ROS level in live cells, the effect of lipopolysaccharide (LPS, an ROS accelerator), N -acetyl- l -cysteine (NAC, an ROS inhibitor), and mitoquinone mesylate (MitoQ, a mitochondrial ROS scavenger) , on TO release in HeLa cells was investigated by a flow cytometry assay. As shown in Figure A, compared with the untreated cells, LPS (ROS accelerator) treatment caused an enhancement of TO fluorescence in cells, and the degree of the enhancement increased with the LPS treatment time.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To further confirm whether IRTO can reflect the change of the mitochondrial ROS level in live cells, the effect of lipopolysaccharide (LPS, an ROS accelerator), N -acetyl- l -cysteine (NAC, an ROS inhibitor), and mitoquinone mesylate (MitoQ, a mitochondrial ROS scavenger) , on TO release in HeLa cells was investigated by a flow cytometry assay. As shown in Figure A, compared with the untreated cells, LPS (ROS accelerator) treatment caused an enhancement of TO fluorescence in cells, and the degree of the enhancement increased with the LPS treatment time.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Also, excessive generation of ROS may stimulate inflammatory processes [18]. Previous work has shown that complexing NAC with Co(II) seems to prevent cobalt-related toxicity in the prostate and periprostatic tissues after injection [7] and that C4 does not prompt excess ROS generation in human cancer cells or normal tongue cells [19]; nevertheless, little was known of the potential for acute or chronic systemic toxicity from C4 in vivo . Here, we showed that a single intramuscular injection of C4 at a concentration 10 times than intended for clinical use, or 100 times more than what would be released from the spontaneous rupture of 120 MRI markers in a human prostate, led to no acute or chronic systemic toxicity or inflammation, no microscopic damage to brain, spinal cord, lung, heart, liver, kidney, or spleen, and no changes in the body or organ weights or in the clinical blood analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Common metals such as copper, cobalt, mercury and zinc also induce ROS production, although an association between ROS production by these compounds and inflammasome activation remains yet to be described [45][46][47][48]. ROS and low-molecular-weight hyaluronic acid (LMWHA) involvement in both priming and activation of the NLRP3 inflammasome.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%